HUBUNGAN ANTARA PENGETAHUAN IBU TENTANG BABY BLUES, PROSES PERSALINAN, DAN PARITAS DENGAN BABY BLUES DI RSIA SRIKANDI IBI KABUPATEN JEMBER - Putri Suci Wulansari (Fakultas Kesehatan Masyarakat, Universitas Jember, 2017)
Baby blues are often ignore so that it is undiagnose and untreate well. This situation can be a problem, because baby blues can progress to more severe emotional disorder that is postpartum depression and even postpartum psychosis. Baby blues can interfere the mother in doing her role as mother, obstruct the producing of oxytocin hormone which is causes the producing of ASI to be reduce. This research is aimed to analyze the relationship between mothers’ knowledge about baby blues, birth process and parity with baby blues at RSIA Srikandi IBI in Jember District.The study was done on 4 October to 3 November 2016 with the type of analytic quantitative research bysectional approach. The total samples were 69 respondents.The analysis of data in this research used the chi square test with 95% significant level (α = 0.05).The analysis result showed that there was no relationship between the level of knowledge about baby and the incident of baby blues at RSIA Srikandi IBI in Jember District (p value = 0.965). The analysis also showed that there was a relationship between birth process and parity with the incident of baby blues at RSIA Srikandi IBI in Jember District (p value 0.002 <0.05) and (p value 0.005 <0.05). Keywords: Baby blues, Knowledge, Birth process, Parity